Penerapan Metode Certainty Factor Untuk Sistem Pakar Dalam Mengidentifikasi Jenis Kerusakan Yang Terjadi Pada Radar Aaws Di Kantor BMKG Medan - Damayanti, Damayanti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
AAWS Radar (Automatic Agroclimate and Weather Station) can also be called automatic agro-climate and weather monitoring post is a tool and installed by BMKG to monitor weather and climate elements automatically and directed to the agricultural sector. With this tool, of course, it can really help BMKG in observing the weather which is certainly useful for agencies from the agricultural sector. Although this radar is very helpful, but when it has been used for a long time it will definitely be damaged. Research with the title